Defamation of the President of Zambia: Contextualising the Decriminalisation Debate - Phiri Christopher (Unisa Press, 2022)
The last two decades have seen a growing global movement towards decriminalising defamation. Numerous calls have been made at various levels for states to repeal all criminal defamation and ‘insult’ laws. Yet many states continue to maintain such laws on the statute books. Zambia is a case in point. This article focuses on the law that criminalises defamation of the President of Zambia, which the authorities have continued to apply with vigour. Diverging from extant judicial precedent upholding the constitutionality thereof, the article argues that that law is unconstitutional and falls foul of international standards on freedom of expression. The article culminates in a call for the decriminalisation of defamation of the President.